Irreversible Electrostatic Deposition of Cdte Quantum Dots on Glassy Carbon Electrodes from Colloidal Solutions - Herrera-Diaz, F; Herrera-Diaz, F (Springer Science and Business Media Deutschland GmbH, 2021)
Cadmium telluride quantum dots (CdTe-QDs) can be deposited from colloidal solutions on glassy carbon (GC) electrodes potentiostatically. The immobilization of QDs can be performed at potentials positive and negative from the potential of zero charge (PZC = 0.45 V vs. Ag/AgCl), including the open circuit potential. The surface coverage of QDs depends on the deposition potential and time. The amount of QD layers was determined by following the redox process of cadmium by cyclic voltammetry and chronoamperometry. Additionally, the QD layers were characterized by scanning electrochemical microscopy (SECM) indicating a decrease of the surface conductivity of GC electrodes. © 2020, Springer-Verlag GmbH Germany, part of Springer Nature.